Analisis Sistem Pengukur Tinggi Badan Pengunjung Butik XYZ menggunakan Microcontroller Arduino Uno dan Sensor Ultrasonic HC-SR04 - Nurul Fajriyah; Wawan Setiawan; Duha, Tobias (Jurnal Informatika, 2023)
The development of this technology makes humans design various tools that can support daily work, such as digital height measuring devices that can work automatically. XYZ Boutique is a clothing boutique located in the Tangerang Regency area. One of the innovations in the application of technology at the XYZ boutique is utilizing microcontroller technology to measure the height of visitors who come. The visitor's height data is used to determine the appropriate clothing model and determine the size and model of clothing. So, boutique employees can offer or recommend clothes according to height. The author uses 3 methods in data collection, namely observation of visits to XYZ boutiques, interviews with boutique owners and employees to find out the problems of tools and equipment needs and conducting journal literature studies related to research conducted by microcontrollers and Ultrasonic Sensors HC-SR04. The result of the research is that a series of automatic height measuring instruments with a microcontroller can be used as an innovation to replace manual height measuring instruments. The results of measuring the height of visitors who come to the boutique will automatically be displayed on the LCD, which can be used as a reference for boutique employee data to recommend clothes based on height grouping.